2019
DOI: 10.1152/ajpregu.00286.2018
|View full text |Cite
|
Sign up to set email alerts
|

Strain-dependent effects on lung structure, matrix remodeling, and Stat3/Smad2 signaling in C57BL/6N and C57BL/6J mice after neonatal hyperoxia

Abstract: Bronchopulmonary dysplasia (BPD) is a chronic lung disease of preterm infants, characterized by lung growth arrest and matrix remodeling. Various animal models provide mechanistic insights in the pathogenesis of BPD. Since there is increasing evidence that genetic susceptibility modifies the response to lung injury, we investigated strain-dependent effects in hyperoxia (HYX)-induced lung injury of newborn mice. To this end, we exposed newborn C57BL/6N and C57BL/6J mice to 85% O2 (HYX) or normoxia (NOX; 21% O2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…On postnatal day 7, we observed that mice reared in hyperoxia exhibited signi cantly lower body weights than did those reared in RA. These results are compatible with those of another study that found hyperoxia to reduce body weight in C57BL/6N mice [21]. In our other studies, we have demonstrated that hyperoxia exposure during the rst 7 days of life induces lung injury, reduces alveolarization and angiogenesis, injures the distal small intestine, disrupts the intestinal barrier, and impairs intestinal function in newborn Sprague Dawley rats [22,23].…”
Section: Discussionsupporting
confidence: 93%
“…On postnatal day 7, we observed that mice reared in hyperoxia exhibited signi cantly lower body weights than did those reared in RA. These results are compatible with those of another study that found hyperoxia to reduce body weight in C57BL/6N mice [21]. In our other studies, we have demonstrated that hyperoxia exposure during the rst 7 days of life induces lung injury, reduces alveolarization and angiogenesis, injures the distal small intestine, disrupts the intestinal barrier, and impairs intestinal function in newborn Sprague Dawley rats [22,23].…”
Section: Discussionsupporting
confidence: 93%
“…One limitation is that this study only used C57BL/6J mice, and mouse strain is an important factor in oxygen sensitivity and airway responses. We chose this strain because it is the most sensitive to hyperoxia-induced perturbations in alveolar development but other strains (BALB/c) are commonly utilized for AHR models, especially in asthma (50,51). We also did not look at other intrapulmonary and extrapulmonary processes that are effected by hyperoxia that we speculate do not relate to pulmonary mechanics.…”
Section: Discussionmentioning
confidence: 99%
“…Work with MHV only requires biosafety level 2 containment as opposed to biosafety level 3 containment when working with SARS-CoV and SARS-CoV-2. Interestingly, even though some coronaviruses are antigenically closely related they are biologically different [30], and pulmonary response in mice is mouse and virus strain-dependent [145,146]. Intranasal inoculation of BALB/c mice with MHV-3, MHV-A59, MHV-1, MHV-S, and MHV-JHM revealed that MHV-1, which is primarily pneumovirulent, produced a transient lung pathology most similar to SARS, which completely resolved by day 21.…”
Section: Mhv As a Model For Sars-cov And Sars-cov-2mentioning
confidence: 99%